Mental State Estimation System for Virtual Meetings with Auditory Modulation - Takano, Fuko; Mano, Hiroaki; Nishii, Yusuke; Miyazaki, Jungo; Kumada, Takatsune (2022 10th International Conference on Affective Computing and Intelligent Interaction Workshops and Demos (ACIIW), 2022)
We are developing a system to estimate and provide feedback on the mental state of individual participants with the aim of assisting videoconference facilitators/moderators as well as the participants themselves. In the present paper, we introduce a system that quantifies signs indicative of the engagement of individual participants in an online meeting by applying auditory modulation.